Development of Learning Media Based on Augmented Reality (AR) Instagram Filter in Shokyu Hyoki 1 - Wiranto Aji Dewandono; Ulfah Sutiyarti; Febi Ariani Saragih (Journal of Japanese Language Education and Linguistics, 2024)
This research aims to provide educational materials for Shokyu Hyoki 1 by utilizing augmented reality filters on Instagram. Utilizing the Sadiman paradigm for media creation. A structured questionnaire was utilized to gather data from 64 students in the class of 2023 enrolled in the Japanese Language Education program at the Faculty of Cultural Sciences, Universitas Brawijaya. The utilization of Augmented Reality (AR) learning tools through Instagram filters was determined to be effective and beneficial for teaching Shokyu Hyoki 1 content. The student response questionnaire shows a high level of approval for the creation of educational materials utilizing augmented reality Instagram filters, scoring 79.5%. This indicates that the media is successful in improving student comprehension and enthusiasm.